KEANEKARAGAMAN SPESIES LAMUN DI KABUPATEN BANGKA SELATAN PROVINSI KEPULAUAN BANGKA BELITUNG - Dwi Rosalina; Endang Yuli Herawati; Yenny Risjani; Muhammad Musa (Universitas Lambung Mangkurat, 2018)
Marine area which is planted by seagrass called as seagrass beds. Seagrass is one of the typical ecosystems in marine waters. Bangka Belitung Province is one of the areas in Indonesia that has seagrass ecosystem. This study aims to determine the diversity, density, and coverage area of seagrass beds in the waters of South Bangka Regency. The research was conducted in Tukak, Tanjung Kerasak, and Tanjung Kemirai. The data is collected using quadratic transect method and also data of physics-chemical parameters such as temperature, salinity, pH, depth, velocity and water substrate. The results of the research showed that 7 species of seagrasses in South Bangka Regency are Cymodocea serrulata, Cymodocea rotundata, Halodule uninervis, Enhalus acoroides, Thalassia hemprichii, Syringodium isoetifolium and Halophila minor. Seagrass in Lempeng waters which has the highest density is Cymodocea serrulata, about 58 ind/m2. The highest frequency of seagrass species in Tukak is Thalassia hemprichii about 1%. Seagrass species of Cymodocea serrulata has the highest cover percentage in Lempeng waters about 29.56%.